2023
DOI: 10.1186/s13018-023-03802-9
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ZFAS1 protects chondrocytes from IL-1β-induced apoptosis and extracellular matrix degradation via regulating miR-7-5p/FLRT2 axis

Abstract: Background Increasing evidence suggested that long non-coding RNAs (lncRNAs) played vital roles in osteoarthritis (OA) progression. In this study, we aimed to reveal the protective roles of lncRNA ZFAS1 in osteoarthritis (OA) and further investigated its underlying mechanism. Methods The chondrocytes were stimulated by IL-1β to establish an in vitro OA model. Then, the expression of ZFAS1, miR-7-5p, and FLRT2 in chondrocytes was determined by qRT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Overexpression of lncRNA ZFAS1 also enhanced cell viability and reduced apoptosis in human chondrocyte cell line CHON-001 via the miR-7-5p/FLRT2 pathway. In addition, IL-1β stimulation upregulated the expression of MMP13 and ADAMTS5 while decreasing the levels of type II collagen and aggrecan in chondrocytes, and these expression changes were abrogated by ZFAS1 overexpression ( Han et al, 2023 ). It has been demonstrated that lncRNA XIST is upregulated in OA cartilage tissue and IL-1β-treated chondrocytes, while apoptosis and ECM expression of chondrocytes are regulated via the miR-149-5p/DNMT3A axis.…”
Section: Regulation Of the Ecm By Lncrnas In Osteoarthritismentioning
confidence: 99%
“…Overexpression of lncRNA ZFAS1 also enhanced cell viability and reduced apoptosis in human chondrocyte cell line CHON-001 via the miR-7-5p/FLRT2 pathway. In addition, IL-1β stimulation upregulated the expression of MMP13 and ADAMTS5 while decreasing the levels of type II collagen and aggrecan in chondrocytes, and these expression changes were abrogated by ZFAS1 overexpression ( Han et al, 2023 ). It has been demonstrated that lncRNA XIST is upregulated in OA cartilage tissue and IL-1β-treated chondrocytes, while apoptosis and ECM expression of chondrocytes are regulated via the miR-149-5p/DNMT3A axis.…”
Section: Regulation Of the Ecm By Lncrnas In Osteoarthritismentioning
confidence: 99%